PERANCANGAN SISTEM INFORMASI GEOGRAFIS STATISTIK KEPOLISIAN (SIGAP) KABUPATEN GORONTALO - Mohamad Ilyas Abas; Rizal Lamusu (Jurnal Ilmu Komputer (JUIK), 2021)
At this time the need for fast, precise and accurate data must be done easily using adequate information technology. The purpose of this research is to make an innovation about the police, both for police administration, crime data, accident-prone and other police data, both in the form of structured data and statistical forms. This system also provides convenience in visualization using a Geographic Information System (GIS) map that displays geographic information on crime data and accident-prone areas so as to provide data information to the police and the public in particular. The system development method used is research and development. This method is very good in developing the system systematically from start to finish at the maintenance stage. The results of this study, in addition to providing a geographic visual display, also provide convenience in terms of information and police statistics in Gorontalo Regency.